PENGARUH INVESTASI SEKTOR PUBLIK TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN ACEH BARAT - Mahrizal Mahrizal (Universitas Teuku Umar, 2018)
Labor Issues Up At The singer still a national problem Enough Weight And different colored WITH ISSUES complex and labor productivity. Labor turmoil form of protest and strike. The low level of education and the lack of protection would affect QUALITY OR Welfare Labor. While the Investment Project is a plan for the review invest resources-Resources, Project both Giant and Small Projects for review acquire Benefits Coming. Singer study conducted at the Department of Industry of West Aceh District. As for Yang Being hearts Research object Research Effect Investment Singer Was Against Labor Absorption ON Industrial Sector in West Aceh district hearts 9-year time span. Interpretation Berdasarkanhasil linear regression, can be known to the contribution of variable Non Against Unrestricted variables, BETWEEN lying investment of 824.9 billion, So that can be concluded that the investment (X) a positive effect against penyerapantenagakerja. With lying words, when investment INCREASES Then it will be followed by increased penyerapantenagakerja. Based on the analysis of R value (correlation coefficient) of 0936, singer correlation value indicates that the relationship between independent variables Namely Investment WITH labor absorption variables including categories are very POWERFUL BECAUSE OF interval 0.8 - 1. In addition ITU findings showed that 85.9 percent Investment variables affect the absorption of manpower in the district of Aceh Barat and 19.1 percent absorption of manpower in West Aceh district is influenced by factors lainnya.Secara t test BETWEEN X (Investment) WITH Y (absorption labor) showed t count = 7,060 WITH significance of 0.000. While t table (a = 0.05; db residual = 7) is at 2,365. BECAUSE t count> t table ie 7060 <2365 So the effect of X is a significant effect ON Error rate a = 5%. It Means singer H0 rejected and H1 accepted, so it can be concluded that labor absorption can be influenced significantly by the variable Investment Operations with the word lie lie that the investment is a factor. Which can be decisive labor absorption Operate Real. In addition to the price BECAUSE THAT LEAD significance Yang Small MORE From 0.05 So investasiberpengaruh Against partial labor in West Aceh district.Keywords: Doble Log, investment, labor Absorption.